Consensus recommendations from the EXPeRT/PARTNER groups for the diagnosis and therapy of sex cord stromal tumors in children and adolescents. (24th March 2021) - Schneider, Dominik T.; Orbach, Daniel; Ben‐Ami, Tal; Bien, Ewa; Bisogno, Gianni; Brecht, Ines B.; Cecchetto, Giovanni; Ferrari, Andrea; Godzinski, Jan; Janic, Dragana; Lopez Almaraz, Ricardo; Pourtsidis, Apostolos; et al.
Abstract: As part of the European Union‐funded project designated Paediatric Rare Tumours Network ‐ European Registry (PARTNER), the European Cooperative Study Group for Pediatric Rare Tumors (EXPeRT) is continuously developing consensus recommendations in order to harmonize standard care for very rare solid tumors of children and adolescents. This paper presents the internationally recognized recommendations for the diagnosis and treatment of sex cord stromal tumors (SCST). The clinical approach to sex cord stromal tumors of the testis (TSCST) and ovary (OSCST) depends on histological differentiation and tumor stage. Virtually all TSCSTs present as localized nonmetastatic tumors, with excellent prognosis after complete resection. In contrast, the prognosis of OSCSTs may be adversely affected by tumor spillage during surgery or presence of metastases. In these cases, cisplatin‐based chemotherapy is recommended. Of note, some SCSTs may develop in the context of tumor predisposition syndromes, for example, DICER‐1, so that specific follow‐up is indicated. SCSTs should be diagnosed and treated according to standardized recommendations that include reference pathology, genetic testing for tumor predisposition syndromes in selected cases, and stratified adjuvant chemotherapy in patients with unfavorable risk profile. To ensure high quality of diagnosis and therapy, patients should be enrolled into prospective registries.